Improving the Performance of the Caterpillar 793C Haul Truck Against Air Pressure Differences Below Mining Wells and Dumping Points: Haul Truck Performance - Fransye Joni Pasau; Gunawan; Fuad Erfan Rifai (Jurnal Rekayasa Mesin dan Inovasi Teknologi, 2023)
The performance of the haul truck engine that operates from the mining well to the dumping point is important in mining operations. Different operational conditions, such as confined environments, low air circulation, exposure to mining particles, and heavy loads, affect engine performance. To achieve efficiency and productivity in operations, analysis of factors that influence unit performance is important. This research analyzes how to improve engine performance by comparing altitude levels which cause differences in atmospheric pressure, which have an impact on haul truck engine performance. Evaluation of heavy equipment engine performance at wells and dumping points shows differences in power, torque and BMEP. In the well, the engine reaches 2331 hp of power, 6862 lb.ft of torque, and BMEP of 138 kg/cm2 at an engine speed of 1784 rpm. Meanwhile at the dumping point, power is 1718 hp, torque is 4748 lb.ft and BMEP is 95.28 kg/cm2 at an engine speed of 1900 rpm. Analysis of the performance of this unit is an important step in facing operational challenges and improving the overall smoothness of mining operations.